PSYCHOMOTOR DOMAIN OF SPEAKING ACTIVITY IN THE ENGLISH TEXTBOOK FOR MALAYSIAN PRIMARY SCHOOL GRADE 4 - Zaqy Mubarok (Faculty of Education and Teachers Training, 2019)
English speaking skill is one of the English skills that is taught in classroom. It deals with human interaction, communication, and connection. Based on the observation in one of the primary schools in Malaysia, the researcher notes some problems in the English learning. There are students’ motivation, overuse of the students in using their native language (Malay), and the students’ dependence on the teacher. Since speaking is a psychomotor skill, psychomotor domain needs to be focused more without ignoring the other domains. This research aims to reveal the types of psychomotor domain used in speaking activity in the English textbook, and to investigate the most dominant type of psychomotor domain used in speaking activity in the English textbook. The type of this research is qualitative research. The researcher implements descriptive qualitative content analysis as the research design. The subject of this research is the speaking learning materials in the English textbook for Malaysia primary school students grade four entitled “English year 4”. The process of analysing data uses the data analysis table of psychomotor domain by Moore (2001).